Anatomical Variants of the Infraorbital Canal: Implications for the Prelacrimal Approach to the Orbital Floor - Li, Lifeng (Am J Rhinol Allergy, 2019)
BACKGROUND: The infraorbital nerve (ION) and its canal are important landmarks during surgical approaches to the orbital floor and pterygopalatine fossa. However, variations in the anatomy of the infraorbital canal and its corresponding neurovascular bundle may impact the access. OBJECTIVE: To investigate anatomic variants of the infraorbital canal from a prelacrimal endoscopic perspective and to explore the impact of these variants on exposing the lateral orbital floor. METHODS: Ten cadaveric specimens (20 sides) were dissected through an endonasal prelacrimal approach. Anatomic variants of the ION including location, branching pattern, and relationship to the infraorbital artery were assessed. The need for ION transposition to increase exposure of the lateral orbital floor was also investigated. RESULTS: Incidence of previously described Types 1, 2, and 3 ION variants were 30.0%, 60.0%, and 10.0%, respectively. Although the orbital floor could be directly accessed in Type 1 and Type 3 IONs, transposition of the ION was necessary to expose the lateral orbital floor in 5 of 12 sides (42%) for Type 2 ION. Bony dehiscence of the orbital floor was identified in 8 of 20 sides (40%) and branching of the ION in 2 of 20 sides (10%). CONCLUSION: Anatomic variations of the infraorbital canal impact surgical exposure of the orbital floor via a prelacrimal approach. Type 1 and Type 3 ION variants allow a direct exposure of the entire orbital floor. A Type 2 ION may require transposition of the nerve to adequately expose the lateral orbital floor.